Pelatihan Aplikasi E-Commerce Desa Cisantana Kuningan Guna Meningkatkan Potensi Ekonomi - Arif Rinaldi Dikananda; Nining Rahaningsih; Irfan Ali (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Cisantana Kuningan Village, in carrying out its entrepreneurship, has used the internet, but the use of this technology has not been optimal. The problem faced by partners is that the use of information technology is still not optimal as a promotional medium for their entrepreneurial products. Partners' limited knowledge and ability to use internet media and e-commerce media is limited to using the WhatsApp application. The solution offered by the PM team is to solve the problems faced by partners by holding training on the use of e-commerce media literacy technology as a product promotion medium. The PM implementation method consists of field surveys, permits, problem analysis, problem solutions, implementation, evaluation and reporting. The output results that will be achieved in this activity are increasing the ability of partners in utilizing information technology and the ability of partners in creating promotional media.